2019
DOI: 10.1371/journal.pone.0222002
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional connectivity of thalamic subdivisions in patients with Parkinson’s disease

Abstract: Parkinson’s disease (PD) affects 2–3% of the population over the age of 65 with loss of dopaminergic neurons in the substantia nigra impacting the functioning of basal ganglia-thalamocortical circuits. The precise role played by the thalamus is unknown, despite its critical role in the functioning of the cerebral cortex, and the abnormal neuronal activity of the structure in PD. Our objective was to more clearly elucidate how functional connectivity and morphology of the thalamus are impacted in PD ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 77 publications
3
8
1
Order By: Relevance
“…The ventral lateral nucleus is the shared node of two important motor circuits, namely the cortico-basal ganglia-thalamocortical circuit and corticocerebello-thalamocortical circuit and is active during both passive and active movements of the contralateral half-body. Increased static FC between the VL/ventral anterior nuclei of the thalamus and the supplementary motor area has been observed in PD patients in a seed-based fMRI study (36). We did not replicate this static FC alteration but identified increased fluctuation of dynamic FC between VL nuclei of the thalamus and PCL in PD-NFOG.…”
Section: Dynamic Fc Between the Thalamic Nuclei And Other Brain Regions In Pdcontrasting
confidence: 60%
See 1 more Smart Citation
“…The ventral lateral nucleus is the shared node of two important motor circuits, namely the cortico-basal ganglia-thalamocortical circuit and corticocerebello-thalamocortical circuit and is active during both passive and active movements of the contralateral half-body. Increased static FC between the VL/ventral anterior nuclei of the thalamus and the supplementary motor area has been observed in PD patients in a seed-based fMRI study (36). We did not replicate this static FC alteration but identified increased fluctuation of dynamic FC between VL nuclei of the thalamus and PCL in PD-NFOG.…”
Section: Dynamic Fc Between the Thalamic Nuclei And Other Brain Regions In Pdcontrasting
confidence: 60%
“…Previous FC investigations in PD implicating the thalamus have yielded inconsistent results with research demonstrating increased coupling between the thalamus and sensorimotor regions (34) or no significant alteration in thalamic FC (35). More recently, a seed-based fMRI FC study demonstrated that PD is associated with increased static FC between the motor subdivisions of the thalamus (VL/ventral anterior nuclei) and the supplementary motor area and between the prefrontal thalamic subdivisions (mediodorsal and anterior nuclei) and the basal ganglia nuclei or anterior and dorsolateral prefrontal cortices (36). A seed-to-voxel static FC study performed with the seeds in the bilateral basal ganglia nuclei, thalamus, and pedunculopontine nucleus revealed that FC of bilateral thalamus and globus pallidus external with visual cortex was significantly increased in PD-FOG compared to PD-NFOG (15).…”
Section: Discussionmentioning
confidence: 99%
“…It also made the work easier as the main task for the investigators was correction of the borders. This process was guided by prior work for striatal structures (Perlaki et al, 2017) and the thalamus (Owens-Walton et al, 2019;Power et al, 2015) as well as our prior work for amygdala and hippocampus segmentation, which is provided in our recent open-access article (Hashempour et al, 2019).…”
Section: Manual Segmentation Of the Subcortical Nucleimentioning
confidence: 99%
“…Typically, the dorsal lateral prefrontal cortex (dlPFC) and thalamus are associated with attention control and cognitive flexibility [ 13 , 33 , 34 ]. Whereas the dlPFC helps to execute tasks that contribute to cognitive functioning, including working memory, attention, and decision-making [ 35 ], the thalamus is critical for enhancing and sustaining cortical connectivity. In recent years, numerous frameworks have begun to acknowledge the prominent role of the thalamus-frontal circuits in attention control and cognitive flexibility [ 34 , 36 38 ].…”
Section: Discussionmentioning
confidence: 99%